FeCoNiB@Boron-doped vertically aligned graphene arrays: A self-supported electrocatalyst for overall water splitting in a wide pH range. (1st August 2021) - Jiang, Bin; Liang, Keming; Yang, Zujin; Guo, Kaiming; Shaik, Firdoz; Zheng, Jianbin
Highlights: A novel strategy has designed for the fabrication of efficient self-supported bifunctional electrocatalysts consist of vertically aligned boron doped graphene (B-VG) integrated with different compositions of iron-based metal borides nanoparticles (IMBs@B-VG) for overall water splitting. Ternary iron-based metal borides exhibited enhanced catalytic activity compared with monometallic and bimetallic borides. FeCoNiB@B-VG exhibited excellent electrocatalytic activity for overall water splitting in a wide pH range, especially in alkaline conditions. Abstract: The development of efficient, cost-effective, bifunctional and self-supported electrocatalysts for overall water splitting in a wide pH range is highly desirable. A novel and highly efficient electrocatalyst for overall water splitting in a wide pH range was synthesized via the electroless plating of FeCoNiB alloy nanoparticles on B-doped vertically aligned graphene arrays (FeCoNiB@B-VG). FeCoNiB@B-VG exhibited excellent electrocatalytic performances with a low overpotential of 31 mV in 1.0 M KOH and 148 mV in 0.5 M H2 SO4 for hydrogen evolution reaction (HER), and an overpotential of 387 mV in 1.0 M KOH for oxygen evolution reaction (OER). It also exhibited a quite low Tafel slope value of 30 mV dec −1 and 51 mV dec −1 for HER and OER in 1.0 M KOH respectively. In addition, FeCoNiB@B-VG also exhibited good long-term stabilities in acidic and alkaline electrolytes as a self-supported bifunctional electrocatalyst. This work may provide theoretical and technical support for design of cost-effective bifunctional electrocatalysts for overall water splitting in a wide pH range. Graphical abstract: Image, graphical abstract